PENGARUH BRAND DAN HARGA TERHADAP TINGKAT HUNIAN KAMARDI DASH HOTEL SEMINYAK - Ni Putu Widiastuti; Mutria Farhaeni; Yanti Elena Sari (Universitas Triatma Mulya, 2021)
This research aimed to analyze the influence of brand and price on room occupancy atDash Hotel Seminyak. The sample of this research is 60 respondents of guests at Dash Hotel Seminyakl. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method, by means of questionnaires with likert scale. The analytical technique used is multiple linier regression analysis. Results of statistical analysis known that the brand and price influenced on room occupancy at Dash Hotel Seminyak is 26,7%, based on hypothesis testing with the F and T testresults, it can be concluded that the brand and price simultaneously (together and significantly influence on room occupancy with value of F-test is 10,402 and sig 0.000 and brand variable (X1) partially and significantly positive influenced on room occupancy (Y)with value of t-test is 2,298 and sig. 0,025 and price variable (X2) significantly positive influenced on room occupancy variable (Y) with value of ttest is 3,076 and sig. 0,003 at DashHotel Seminyak.